Longitudinal Intravital Microscopy Reveals Axon Degeneration Concomitant With Inflammatory Cell Infiltration in an LPC Model of Demyelination - El Waly, Bilal; Buttigieg, Emeline; Karakus, Cem; Brustlein, Sophie; Debarbieux, Franck (Frontiers in Cellular Neuroscience, 2020)
Demyelination and axon degeneration are the central events in all neurodegenerative diseases, including multiple sclerosis. Intoxication of oligodendrocytes with lysophosphatidylcholine (LPC) is often used as a selective model of focal and reversible demyelination thought to have no incidence for neurons. To characterize the cascade of cellular events involved in LPC induced demyelination, we have combined intravital Coherent anti-stoke Raman scattering microscopy with intravital two-photon fluorescence microscopy in multicolor transgenic reporter mice. Moreover, taking advantage of a unique technique of spinal glass window implantation, we here provide the first longitudinal description of cell dynamics in the same volume of interest over weeks after insults. We have detected several patterns of axon-myelin interactions and classified them in early and advanced events. Unexpectedly, we have found that oligodendrocyte damages in fact lead to axon degeneration within 2 days after LPC incubation and this degeneration is amplified after the recruitment of the peripheral inflammatory cells at day 4. Beyond day 7, the recovery of axon number and myelin takes 3 more weeks post lesion and involves a new wave of innate immune cells at day 14. Therefore, recurrent imaging over several weeks suggests an important role of peripheral immune cells in regulating both the axonal and oligodendroglial fates, and thereby the remyelination status. Better understanding the recruitment of peripheral immune cells during demyelinating events should help to improve diagnosis and therapy.